2015
DOI: 10.1037/a0038707
|View full text |Cite
|
Sign up to set email alerts
|

A review of the content, criterion-related, and construct-related validity of assessment center exercises.

Abstract: This study uses meta-analysis and a qualitative review of exercise descriptions to evaluate the content, criterion-related, construct, and incremental validity of 5 commonly used types of assessment center (AC) exercises. First, we present a meta-analysis of the relationship between 5 types of AC exercises with (a) the other exercise types, (b) the 5-factor model of personality, (c) general mental ability (GMA), and (d) relevant criterion variables. All 5 types of exercises were significantly related to criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 131 publications
5
40
1
3
Order By: Relevance
“…When reviewing the effect sizes across the three samples, the difference was more pronounced on the IB exercise (Sample 1: d = 0.95; Sample 2: d = 0.73; Sample 3: d = 0.56). This finding is in line with our original hypothesis, showing alignment to previous research (Goldstein et al, 1998;Hoffman et al, 2015), although the magnitude of these differences were larger for this study. The implication of this finding is that the IB exercise is potentially unsuitable for organizations operating in culturally diverse settings and highlights the impact of political, economic, and societal factors at work in these environments.…”
Section: Independent Samples T-test and Cohen's Dsupporting
confidence: 94%
See 1 more Smart Citation
“…When reviewing the effect sizes across the three samples, the difference was more pronounced on the IB exercise (Sample 1: d = 0.95; Sample 2: d = 0.73; Sample 3: d = 0.56). This finding is in line with our original hypothesis, showing alignment to previous research (Goldstein et al, 1998;Hoffman et al, 2015), although the magnitude of these differences were larger for this study. The implication of this finding is that the IB exercise is potentially unsuitable for organizations operating in culturally diverse settings and highlights the impact of political, economic, and societal factors at work in these environments.…”
Section: Independent Samples T-test and Cohen's Dsupporting
confidence: 94%
“…In addition to accounting for the general effectiveness of participants, research on the GPF in AC ratings indicates, for example, a relationship to cognitive ability (Hoffman et al, 2011) and conscientiousness (Lance et al, 2007). These findings resonate with research demonstrating that cognitive ability predicts candidate performance in AC exercises (Hoffman et al, 2015) and AC dimensions (Meriac et al, 2014). We can therefore assert that the presence of a GPF in AC ratings might reflect cognitive ability to some extent:…”
Section: Gpf In Acssupporting
confidence: 52%
“…Moreover, B. J. Hoffman et al (2015) found small-to-moderate criterion-related validities associated with individual AC exercises.…”
Section: Exercise-versus Dimension-centric Perspectivesmentioning
confidence: 94%
“…Past research that studied the nomological network of AC ratings involved the overall assessment rating (e.g., Collins et al, 2003), final dimension ratings (Dilchert & Ones, 2009;Meriac, Hoffman, & Woehr, 2014;Shore, Thornton, & Shore, 1990), overall exercise ratings (Hoffman, Kennedy, LoPilato, Monahan & Lance, 2015), or latent exercise factors together with the latent general performance factor (Lance et al, 2007) and their relationships with the Big Five and general mental ability (GMA). However, this research allows only limited inferences with regard to the constructrelated validity of the different latent components that constitute AC performance, namely, dimensions, exercises, and general performance (Hoffman et al, 2011) relative to each other.…”
Section: Nomological Network Of Ac Factorsmentioning
confidence: 99%